Communication Management Of Gampong Apparatus In Community Service - Firdaus Fadhli (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Apparatus Gampong is a social group that functions to help meet the needs of rural communities, given the obligations and rights that have been determined by the Indonesian state. In realizing the welfare of the community, the gampong is a subsystem of government administration. There are various needs of the community that must be met by the gampong, to avoid this interaction conflict, the gampong requires a communication system to maintain a harmonious and structured interaction. Therefore, this study aims to determine the communication management needed by the gampong apparatus in community service and the application of communication management of the gampong apparatus in community service in Samatiga District, West Aceh Regency. The research approach uses qualitative descriptive analytical methods to examine social phenomena on research subjects, namely Keuchik and the Gampong, Tuha Peut, the people in Kuala Bubon Village, Paya Lumpat Village, and Pange Village, as well as the Samatiga Subdistrict Head in Samatiga District. Sources of data obtained through observation, and interviews. The results of the study indicate that communication management facilitates the gampong apparatus in implementing community service activities with a systematic and structured communication flow. The implementation of communication management is carried out by the gampong apparatus with the stages of planning for service activities needed by the community, then determining the implementation of activities, distributing policies for community service activities, and controlling community service activities so that communication flow is maintained in accordance with the service program design that has been formed.